2021
DOI: 10.2196/23835
|View full text |Cite
|
Sign up to set email alerts
|

A Virtual Reality–Based App to Educate Health Care Professionals and Medical Students About Inflammatory Arthritis: Feasibility Study

Abstract: Background Inflammatory arthritides (IA) such as rheumatoid arthritis or psoriatic arthritis are disorders that can be difficult to comprehend for health professionals and students in terms of the heterogeneity of clinical symptoms and pathologies. New didactic approaches using innovative technologies such as virtual reality (VR) apps could be helpful to demonstrate disease manifestations as well as joint pathologies in a more comprehensive manner. However, the potential of using a VR education con… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 30 publications
0
6
0
1
Order By: Relevance
“…Despite the diversification of virtual simulators/platforms/systems used in undergraduate medical education, we found that 48 (52%) studies ( 18 , 22 , 23 , 27 31 , 33 35 , 37 39 , 42 , 44 48 , 50 , 52 , 54 , 57 67 , 71 , 72 , 75 , 78 , 81 84 , 93 , 96 , 99 , 101 , 103 , 105 ) reported the immersive VR application, which is characterized by the use of VR equipment consisting of head-mounted displays (headsets or goggles) and/or hand controllers. This finding suggested that VR might be a typical and popular representative of modern VS technology used in medical education.…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…Despite the diversification of virtual simulators/platforms/systems used in undergraduate medical education, we found that 48 (52%) studies ( 18 , 22 , 23 , 27 31 , 33 35 , 37 39 , 42 , 44 48 , 50 , 52 , 54 , 57 67 , 71 , 72 , 75 , 78 , 81 84 , 93 , 96 , 99 , 101 , 103 , 105 ) reported the immersive VR application, which is characterized by the use of VR equipment consisting of head-mounted displays (headsets or goggles) and/or hand controllers. This finding suggested that VR might be a typical and popular representative of modern VS technology used in medical education.…”
Section: Resultsmentioning
confidence: 84%
“…In addition to the above learning contexts and practical aspects, the remaining 18 articles ( 15 , 21 , 24 , 27 , 40 , 41 , 43 , 54 , 73 , 77 , 83 , 87 , 89 , 95 , 100 , 102 , 103 , 105 ) reported the integration of VS into other case-based learning experiences in virtual patient-care settings. Despite the diversity of virtual patient systems and clinical scenarios, these studies generally showed that VS-integrated case-based learning as a feasible teaching approach ( 54 ) could result in students’ learning gains, retention of information, and transfer of knowledge to clinical application ( 89 , 95 , 100 , 102 ), help future physicians improve diagnostic accuracy thus enhance the clinical reasoning teaching ( 15 , 27 , 43 ), extend students’ preparedness level for their future clinical experiences ( 40 , 83 ), facilitate empathy ( 24 ), cultural competence ( 77 ) and comprehensive clinical skills such as communication-based skills ( 21 ), clinical decision-making skills ( 78 ) within undergraduate medical education, and improve students’ confidence in managing clinical scenarios ( 41 ), thus was highly received by students ( 89 , 95 , 105 ).…”
Section: Resultsmentioning
confidence: 99%
“…Demonstration of such images to patients is easy, fast and therefore feasible in daily clinical practice. It is also conceivable that in the future this data cannot only be offered via images but also through immersive technologies such as augmented reality, mixed reality (like Hololens) or virtual reality* ( 16 , 17 ). This might even enhance the proven effect of those immersive applications in the context of teaching medical students or health care professionals improve their knowledge and disease understanding and thus empathize the patients’ symptoms and functional disabilities.…”
Section: Discussionmentioning
confidence: 99%
“…Dabei wurde das System für die VR-Applikation „Rheumality©“ (Lilly Deutschland GmbH, Bad Homburg v. d. H., Deutschland) fest in den Lehrräumen des SkillsLabs installiert, und die Tutorinnen und Tutoren wurden für die selbstständige Anwendung instruiert. Eine in diesem Zusammenhang veröffentlichte Publikation unserer Arbeitsgruppe zeigte, wie eine erste Version unserer Applikation, die 2‑D- und 3‑D-Daten der pathologischen Gelenke von echten Patientinnen und Patienten mit rheumatoider Arthritis und Psoriasisarthritis in verschiedenen Stadien der Krankheit zum besseren Verständnis der Erkrankungsbilder – nicht nur bei Medizinstudierenden, sondern auch bei Patientinnen und Patienten und sogar bei Rheumatologinnen und Rheumatologen in der Weiterbildung – führt [ 6 , 9 ]. Auf Grundlage dieses wertvollen Feedbacks wird fortlaufend der Funktionsumfang der Applikation erweitert.…”
Section: Fragestellungunclassified